2022
DOI: 10.5423/ppj.oa.12.2021.0189
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Changes in Lucerne (Medicago sativa) Plants Infected with ‘Candidatus Phytoplasma australasia’-Related Strain (16SrII-D Subgroup)

Abstract: Changes in physiological and biochemical patterns in lucerne plants caused by the presence of ‘Candidatus Phytoplasma australasia’, which is one of the significant pathogens causing yield losses in lucerne plants, were investigated. Significant differences were evident in total chlorophyll, chlorophyll a, chlorophyll b, and protein amounts between ‘Ca. Phytoplasma australasia’-positive and negative lucerne plants. Stress-related metabolites such as phenol, malondialdehyde, and proline accumulations in ‘Ca. Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Similarly, the increases in total phenolic contents followed by phytoplasma infection were evident in pepper and alfalfa plants (Ayvaci et al, 2022;Reveles-Torres et al, 2018). Increases in proline and phenol contents in almond leaves are strong parameters that the plant reacts to the pathogen attack and goes on defensive stages.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Similarly, the increases in total phenolic contents followed by phytoplasma infection were evident in pepper and alfalfa plants (Ayvaci et al, 2022;Reveles-Torres et al, 2018). Increases in proline and phenol contents in almond leaves are strong parameters that the plant reacts to the pathogen attack and goes on defensive stages.…”
Section: Discussionmentioning
confidence: 94%
“…There are quite a few studies containing CAT and POD enzyme activities in phytoplasma infections in pistachio trees (Akkurak et al, 2021), and alfalfa (Ayvaci et al, 2022), corn (Junqueira et al, 2004), lime (Zafari et al, 2012), mungbean (Hameed et al, 2017) plants. In addition to these studies, Ranjbar et al (2022) reported increased CAT and POD enzyme activities in almond trees exposed to drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations